1
$\begingroup$

While scanning this online pdf, I came across a possible mistake?

From $(12)$ to $(14)$, the PDF starts with $$p\{[p+a_2-(a_3^2/4)]^2-4a_0\}=\{(a_3/2)[p+a_2-(a_3^2/4)]-a_1\}^2\tag{12}$$

And ends up with the cubic $$p_1^3-a_2p_1^2+(a_1a_2-4a_0)p_1+4a_0F_1-a_1^2=0\tag{14}$$ where $F_1=a_2-(a_3^2/4)$ and $p_1=p+F_1$ With $a_3,a_2,a_1,a_0$ coefficients of the quartic such that it is $x^4+a_3x^3+a_2x^2+a_1x+a_0=0$. But with their example, starting with a quartic $x^4-x^3-19x^2-11x+30=0$ they found that it as a corresponding cubic of $$p_1^3+19p_1^2-109p_1-2431=0$$ but when I computed $a_1a_2-4a_0$, I get a different answer. Namely, $(-19)\cdot(-11)-4\cdot 30=89$ Which is no where near $-109$.

Am I doing something wrong, or does the PDF have a little mistake?

$\endgroup$
1
$\begingroup$

Am I doing something wrong, or does the PDF have a little mistake?

I think the latter. The following should be correct : $$p_1^3-a_2p_1^2+(a_1a_\color{red}{3}-4a_0)p_1+4a_0F_1-a_1^2=0\tag{14}$$ since from $(12)$ we get $$(p_1-F_1)(p_1^2-4a_0)=\left(\frac{a_3}{2}p_1-a_1\right)^2,$$ i.e. $$p_1^3-4a_0p_1-F_1p_1^2+4a_0F_1=\frac{a_3^2}{4}p_1^2-a_1a_\color{red}{3}p_1+a_1^2$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.